Tales from a not-so-perfect pet sitter / 10. - Russell, Nikki; Russell, Erin (Dork diaries, 2015)
"Nikki has to hide seven ADORKABLE puppies from two parents, one nosy little sister, an entire middle school, and one mean girl out for revenge, Mackenzie Hollister. If anyone can do it, it's Nikki--but not without some ... challenges along the way!"-Amazon.com.